Sweet tooth eaudiobook - McEwan, Ian (Recorded Books Inc., 2012)
Winner of such prestigious honors as the Booker Prize and Whitbread Award, Ian McEwan is justifiably regarded as a modern master. Set in 1972, Sweet Tooth follows Cambridge student Serena Frome, whose intelligence and beauty land her a job with England's intelligence agency, MI5. In an attempt to monitor writers' politics, MI5 tasks Serena with infiltrating the literary circle of author Tom Healy. But soon matters of trust and identity subvert the operation.